Mando et Lego: as pontes nos testamentos eclesiásticos portugueses (1071 a 1325) - Conceição, Rúben Filipe Teixeira da (Lusitania sacra, 2021)
Through the analysis of the wills of the ecclesiastics inserted in the Testamenta Ecclesiae Portugaliae (between 1071, the year of the restoration of the Archdiocese of Braga, and 1325, the end of the reign of D. Dinis), we intend to identify the changes and continuities in relation to the bridges existing in the territory of the medieval Portugal, as well as to examine their distribution in space, the values and assets left by legacy for the construction or maintenance of these structures and ascertain the existence or not of temporal and spatial tendencies.